Biomimetics: forecasting the future of science, engineering, and medicine - Hwang J (Dove Medical Press, 2015)
Jangsun Hwang,1 Yoon Jeong,1,2 Jeong Min Park,3 Kwan Hong Lee,1,2,4 Jong Wook Hong,1,2 Jonghoon Choi1,2 1Department of Bionano Technology, Graduate School, Hanyang University, Seoul, 2Department of Bionano Engineering, Hanyang University ERICA, Ansan, Korea; 3Department of Biomedical Engineering, Boston University, 4OpenView Venture Partners, Boston, MA, USA Abstract: Biomimetics is the study of nature and natural phenomena to understand the principles of underlying mechanisms, to obtain ideas from nature, and to apply concepts that may benefit science, engineering, and medicine. Examples of biomimetic studies include fluid-drag reduction swimsuits inspired by the structure of shark’s skin, velcro fasteners modeled on burrs, shape of airplanes developed from the look of birds, and stable building structures copied from the backbone of turban shells. In this article, we focus on the current research topics in biomimetics and discuss the potential of biomimetics in science, engineering, and medicine. Our report proposes to become a blueprint for accomplishments that can stem from biomimetics in the next 5 years as well as providing insight into their unseen limitations. Keywords: biomimicry, tissue engineering, biomaterials, nature, nanotechnology, nanomedicine